Smart territorial relationships: A conceptual framework to cope with the rural-urban divide in mountainous regions. - Ravazzoli, Elisa; Götsch, Helena; Hoffmann, Christian (Springer, 2018)
So far, the literature discussed rural-urban linkages as an instrument that has the capacity to reduce the rural-urban divide and to improve the living conditions of rural and mountainous areas. However, structural changes in the economy and society and advances in transportation and communication technology, as well as transformations in the cities' functions and structures, have significantly modified the dynamics between rural and urban areas from a unidirectional relationships to multidimensional ones. Interactions today happen in non-contiguous spaces; they occur in a broad territorial space that is no longer limited to geographical boundaries. In order to understand the new types of relationships that are occurring today between various territories and to comprehend their nature we believe it is necessary to develop a new conceptual framework. A new conceptual framework, based on the concept of 'smart-territorial relationships', will enable planners to re-frame, adapt, explain and describe linkages and interactions as they currently appear in our society.
Keywords: Regionalplanung; Erreichbarkeit; Infrastruktur; Digitalisierung; Standortfaktor; Ländlicher Raum